2016
DOI: 10.1371/journal.pone.0161602
|View full text |Cite
|
Sign up to set email alerts
|

SOFI Simulation Tool: A Software Package for Simulating and Testing Super-Resolution Optical Fluctuation Imaging

Abstract: Super-resolution optical fluctuation imaging (SOFI) allows one to perform sub-diffraction fluorescence microscopy of living cells. By analyzing the acquired image sequence with an advanced correlation method, i.e. a high-order cross-cumulant analysis, super-resolution in all three spatial dimensions can be achieved. Here we introduce a software tool for a simple qualitative comparison of SOFI images under simulated conditions considering parameters of the microscope setup and essential properties of the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…In previous work we and other groups demonstrated that super-resolution optical fluctuation imaging (SOFI) is well suited to live-cell super-resolution imaging5678, due to its ability to image in challenging conditions such as low signal to noise and high background9. The technique operates by analyzing spontaneous fluctuations in fluorophore emission that arise through blinking, made observable by analyzing multiple (100 or more) fluorescence images rapidly acquired from the same sample.…”
mentioning
confidence: 99%
“…In previous work we and other groups demonstrated that super-resolution optical fluctuation imaging (SOFI) is well suited to live-cell super-resolution imaging5678, due to its ability to image in challenging conditions such as low signal to noise and high background9. The technique operates by analyzing spontaneous fluctuations in fluorophore emission that arise through blinking, made observable by analyzing multiple (100 or more) fluorescence images rapidly acquired from the same sample.…”
mentioning
confidence: 99%
“…We simulated the acquisition of K = 10 images of size N = 64 over 0.1 sec using the molecule distribution of the microtubules dataset (MT0) from the SMLM challenge 2016, 3 containing 8 731 molecules. The temporal blinking profiles were generated using the SOFI simulation tool [16], as described in Section 3.3. The ground truth and observed image (with a 5× zoom) of Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…1, where five stacks of 20 molecules uniformly distributed over the border of a square with varying side length are processed. The temporal profiles were generated with the SOFI simulation tool [16] and are discretized realizations of a continuous-time Markovian process with emitting (average lifetime τ on = 20 ms), dark (τ off = 40 ms) and bleached (average emitting time until bleaching τ bl = 80 s) states. The number of photons per frame of an emitting molecule is a Poisson variable with mean 400.…”
Section: P ) As the Matrix Between Parentheses In This Expression Eqmentioning
confidence: 99%
“…SOFI analysis was carried out as reported previously [ 49 ]. We used a custom written algorithm (Matlab, The Mathworks) based on the code of our SOFI simulation tool [ 51 ] and the bSOFI algorithm [ 50 ]. The sequence of camera frames was divided into subsequences of 500 frames each.…”
Section: Methodsmentioning
confidence: 99%